Surgical Treatment of Varicose Veins of the Lower Extremities - I. P. Mikhailov; B. V. Kozlovsky; V. A. Arustamyan (Неотложная медицинская помощь, 2023)
The review presents an analysis of relevant literature on the surgical treatment of varicose veins of the lower extremities. Modern methods of surgical intervention for varicose veins are considered: open operations, methods of thermal ablation of the main veins, non-thermal non-tumescent methods, vein-preserving surgery (ASVAL), methods of treating reflux in perforating veins and recurrent varicose veins. The effectiveness of each of the surgical treatment methods used was analyzed. The frequency of relapses and the likelihood of complications of the described operations are considered. All surgical treatment methods presented in the review were developed on the basis of modern ideas about the pathogenesis of varicose veins, the mechanisms of formation of chronic venous insufficiency, and have an evidence base. These techniques are reflected in the latest clinical guidelines and are widely used in medical practice.